FORMATION AND TRAINING OF YOUNG NERS CADRES WITH EDUCATIONAL GAMES SNAKES AND LADDERS - Eva Oktaviani; Susmini Susmini; Jhon Feri (JCES (Journal of Character Education Society), 2021)
Abstrak: Anak usia sekolah berjumlah 30% dari masyarakat di Indonesia. Anak pada usia tersebut sangat penting dibekali pemahaman tentang kebiasan perilaku hidup bersih sehat karena beresiko terkena penyakit. Upaya promosi kesehatan di sekolah akan lebih efektif dengan menggunakan pendekatan sebaya. Optimalisasi hasil dalam rangka kegiatan tersebut, perlu dibentuk dan dilatih siswa sekolah dasar menjadi kader kesehatan sekolah yang disebut Ners Cilik. Tujuan kegiatan pengabdian kepada masyarakat ini adalah pembentukan Kader Ners Cilik sebagai bentuk upaya pemberdayaan masyarakat di sekolah dasar, sehingga dapat berperan sebagai agen perubahan penggerak perilaku hidup bersih dan sehat. Kader Ners Cilik dipilih dari kelas 4 dan 5 SD Uswatun Hasanah berjumlah 20 orang yang telah mengikuti pelatihan. Peningkatan pengetahuan dilakukan dengan bentuk penyuluhan kesehatan dengan metode permainan edukatif ular tangga yang berisikan pertanyaan seputar PHBS dan P3K. Hasil evaluasi terlihat ada peningkatan nilai rerata pre dan posttest. Rerata pengetahuan PHBS dari nilai 78,25 meningkat menjadi 91,75 dan rerata pengetahuan P3K dari nilai 61,25 meningkat menjadi 80. Pembentukan Kader Ners Cilik diharapkan dapat dibentuk sejak dini sebagai upaya pelayanan kesehatan sederhana di lingkungan sekolah.Abstract: School age-children is 30% of the people in Indonesia. It is very important for children at that age to be equipped with an understanding of clean and healthy living habits because they are at risk of getting disease. Health promotion efforts in schools will be more effective by using a peer approach. Optimizing the results in the context of these activities, it is necessary to form and train elementary school students to become school health cadres called Little Nurses. The aim of this community service activity is the formation of a cadre of young nurses as a form of community empowerment in elementary schools, so that they can act as agents of change in driving clean and healthy living behavior. The cadres of Little Nurses were selected from the 4th and 5th grades of SD Uswatun Hasanah totaling 20 people who had attended the training. Knowledge improvement is carried out in the form of health education with the snake and ladder educational game method which contains questions about PHBS and first aid. The results of the evaluation showed that there was an increase in the mean pre and posttest scores. The average PHBS knowledge increased from 78.25 to 91.75 and the average P3K knowledge increased from 61.25 to 80. The formation of a cadre of little nurses is expected to be formed early on as an effort to provide simple health services in the school environment.